Innovative Use of Endogenous Enzymes to Enhance Silage Chemical Quality of Corn Straw for Buffalo (Bubalusbubalis) Feed in Samosir Island - Ginting, Nurzainah; Mirwandhono, Raden Edhy; Purba, Muhammad Adanan; Nasution, Muhammad Amran; Saragih, Winda Fransisca; Ketaren, Nurjama’yah br.; Samsudin, Anjas Asmara (Journal of Buffalo Science, 2025)
On Samosir Island, there is an annual shortage of buffalo feed during the dry season. However, this feed shortage has caused farmers to scramble to find substitute feed. Still, it has also caused stress in the buffalo, which has led to the emergence of Haemorrhagic septicemia (HS), as Samosir is an endemic area (HS). Beginning in 2024, corn cultivation began to be widely practiced on the island of Samosir, which generates a significant amount of waste such as corn straw. This research focuses on preparing feed for buffalo (Bubalus bubalis) using fermented corn straw, with the fermentation process utilizing endogenous enzymes derived from rumen fermentation (EERF). It was obtained from fermented 100- day buffalo rumen, where the buffalo rumen comes from buffalo that consume corn straw. This study used a completely randomized design, a 3×3factorial with three replications. Factor I was various doses of EERF(2%, 4%,6%),and Factor II was different fermentation times(5d,10d, 15d).Parameters that were observed in this study were chemical quality: Dry Matter (DM), Neutral Detergent Fiber (NDF), Acid Detergent Fiber (ADF), Crude Protein (CP), and pH. Previously, isolation on EERF was carried out to identify the dominant fiber-degrading colonies, as they produce enzymes. Analysis of the potential of corn straw for buffalo feed was conducted by calculating corn straw production from the corn harvest area on Samosir Island. The result of this study is that corn straw fermentation using endogenous enzymes improves the chemical quality of silage, such as DM increasing from 38.59 to 46.17, NDF from 46.23 to 40.48, ADF from 30.53 to 24.21, CP from 9.25 to 9.86, and pH from 5.15 to 4.76. Through this improvement in nutritional quality, the dietary needs of buffaloes are met. This corn straw is sufficient for 9,565,101 buffaloes. Since corn cultivation has become intensive, there is a tendency of HS cases to decrease, with only 6 instances of HS in 2024 and 13 cases up to June 2025, while in 2023 there were 202 cases.